My Butt Has Touched Every Surface In This House - Miller, Dani (Cornfield Review, 2019)
While watching my cat lay move around the house and sit down, it made me realize that because of the way she sits, her butt has touched every surface in the house. No surface is safe from a cat butt, but this is the life I chose to have.